2007
DOI: 10.1007/s11604-006-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of regional left ventricular wall thickness and thickening using 16 multidetector-row computed tomography: comparison with cine magnetic resonance imaging

Abstract: MDCT is a feasible method to assess regional LV wall thickness and systolic thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…17 Previous research found a significant correlation between MDCT and MRI for anatomic LV parameters, such as ESWT, EDWT, and the dynamic LV parameter of WT, and concluded that MDCT can accurately estimate regional LV wall thickness and WT. 18,19 In the present study, all regional LV anatomic and dynamic CE-CT parameters differed significantly between abnormal and normal voltage segments. Multivariate stepwise logistic regressions demonstrated that the statistical prediction model including ESWT and WT resulted in an AUC of 0.85Ϯ0.05, which correctly classified 81.7% of the voltage segments into the abnormal category.…”
Section: Regional Anatomic Dynamic Parameters and Perfusion Charactsupporting
confidence: 42%
“…17 Previous research found a significant correlation between MDCT and MRI for anatomic LV parameters, such as ESWT, EDWT, and the dynamic LV parameter of WT, and concluded that MDCT can accurately estimate regional LV wall thickness and WT. 18,19 In the present study, all regional LV anatomic and dynamic CE-CT parameters differed significantly between abnormal and normal voltage segments. Multivariate stepwise logistic regressions demonstrated that the statistical prediction model including ESWT and WT resulted in an AUC of 0.85Ϯ0.05, which correctly classified 81.7% of the voltage segments into the abnormal category.…”
Section: Regional Anatomic Dynamic Parameters and Perfusion Charactsupporting
confidence: 42%
“…The ratio of wall thickness to radius of curvature is an index of LV wall stress (σ) as derived from the Laplace’s Law (P 9 R = σ 9 T, i.e., σ/P = R/T), where P is the transmural pressure. We chose the upper limit of left ventricular free-wall thickness to be 11.5 mm based on the published ultrasound [1416] and MRI [15] data.…”
Section: Methodsmentioning
confidence: 99%
“…Contrast-enhanced multidetector computed tomography (MDCT) has been shown to provide not only myocardial and vascular anatomy, but also myocardial wall thickness with submillimetric resolution. 9,10 Myocardial wall thinning (WT) has been reported to correlate with endocardial low voltage, 11 but the epicardial voltage and its relationship with LAVA have not been investigated. The objectives of this study were to quantify the relationship between the regional myocardial WT as imaged by MDCT and voltage-defined endo-and epicardial scar, and to assess how regional myocardial WT might predict distribution and characteristics of LAVA.…”
mentioning
confidence: 99%